معالجة التأثير الموسمي على التقطير الشمسي في ولاية الوادي - أسماء, ميده; منال, صغيري (universty of elouedجامعة الوادي, 2020)
"الملخص: الصحراء الجزائرية تعاني من ندرة مياه الشرب, الامر الذي ادى الى تحفيز العلماء الى البحث عن تقنيات جديدة لتحلية المياه, من بين هذه التقنيات تقنية التقطير الشمسي الذي يعتبر من أبسط التقنيات لحل هذه المشكلة, غير أن مشكلة أخرى تظهر وهي تدني الربحية في الشتاء لأن المناطق الصحراوية الجزائرية تتميز بالحرارة الشديدة صيفا والبرودة شتاءا. تهدف دراستنا هذه الى التغلب على هذه الصعوبة من خلال تعديل الإعداد التجريبي في فصل الشتاء في المناطق الجافة الجزائرية بإضافة معزز (جزيئات نانوية) لتعويض ضعف الإشعاع الشمسي. لهذا نقوم بدراسة إنتاجية التقطير الشمسي في الصيف وفي الشتاء مع وبدون نظام محسن. حيث تؤكد النتائج التجريبية أن إنتاجية المقطر غير المحسن في الصيف أفضل 2.4 مرة من إنتاجية التقطير غير المحسن في الشتاء وتصل إلى 1.7 ضعف إنتاجية المقطر المحسن مع جزيئات Al2O3 النانوية في الشتاء. عند مقارنة الإنتاجية خلال فصل الشتاء تبين أن إنتاجية المقطر المحسن بجزيئات Al2O3 النانوية أفضل 1.4 مرة من إنتاجية المقطر غير المحسن ، وتظهر النتائج التي تم الحصول عليها بوضوح الفرق في إنتاجية الماء المقطر بين الموسمين. لذلك يوصى باستخدام جهاز التقطير المحسن في الشتاء وجهاز التقطير التقليدي في الصيف في مثل هذه المناطق. ""Abstract: The Algerian desert suffers from a scarcity of drinking water, which has prompted scientists to search for new technologies for water desalination. Among these technologies is solar distillation technology, which is considered one of the simplest techniques to solve this problem, but another problem appears which is the low profitability in winter because the regions The Algerian desert is characterized by extreme heat in summer and cold in winter. Our study aims to overcome this difficulty by modifying the experimental setup in the winter season in the Algerian dry regions by adding a booster (nanoparticles) to compensate for the weak solar radiation. That is why we study the productivity of solar distillation in summer and winter with and without an optimizer system. The experimental results confirm that the yield of unimproved distillate in summer is 2.4 times better than that of unimproved distillation in winter and up to 1.7 times that of the enhanced distillate with Al2O3 nanoparticles in winter. When comparing the productivity during the winter season, it was found that the yield of the improved distillate with Al2O3 nanoparticles is 1.4 times better than that of the unimproved distillate, and the results obtained clearly show the difference in the yield of distilled water between the two seasons. Therefore it is recommended to use the enhanced distillation apparatus in winter and the conventional distillation apparatus in the summer in such areas "
مذكرة تخرج ماستر فيزياء
Keywords: الكلمات المفتاحية: تحلية المياه؛ ماء الشروب؛ فصل الشتاء؛ فصل الصيف؛ الطاقة الشمسية؛ الجسيمات النانوية Al2O3; Keywords: Desalination; Drinking Water; Winter Season; Summer Season; Solar Energy; Al2O3 Nanoparticles.